Development of motion response training system for badminton applicable also to table tennis - Kuo, K.-P. (Proceedings Book of The 16th ITTF Sports Science Congress Budapest (HUN), April 19th - 20th, 2019, 2020)
This project is to implement the sports science professional to design and develop the badminton agility reaction training equipment with intelligent functions to assist players` training and monitoring. Product design with a Bluetooth wireless function of the LED lamp module, with the development of the APP system program, so that the operating interface simple and easy to understand. Products with functions to sub-timing, training mode, test and record, feedback and so on. Objective: First of all, design and develop a badminton visual action reaction training system based on cross-field design, which provided agility, assistance and monitoring of the badminton footwork. Second, the design can meet the needs of domestic training, and the product has the features of wisdom and the lower cost. Method: The design of product architecture is designed with LED lamps, infrared sensor modules, and programmable controllers to operate the interface by the touch panel. The product has functions such as segment timing, step training, game simulation mode, testing, recording, and feedback. Results: The visual action reaction training system with the characteristics of auxiliary training, monitoring, testing, recording and the lower cost. It can precisely record the sports time, reaction time, action time in all directions and the simulation game. What`s more, do the analysis through the built-in formula to output the action time pattern. And in the next study we will apply to the training of table tennis and tennis.